1989
DOI: 10.1016/1010-7940(89)90024-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and bronchoplastic resection for bronchial carcinoid tumours

Abstract: From January 1974 to December 1987, 45 cases of bronchial carcinoid were surgically managed at our Unit, 44 of which were evaluated. All patients but 2 were submitted to fiberoptic bronchoscopy prior to surgery. A standard resection was performed in 19 cases (13 lobectomies, 4 bilobectomies and 2 pneumonectomies). In 11 cases, pulmonary resection was complemented with a bronchoplastic technique (6 lobectomies, 2 bilobectomies, 2 pneumonectomies, 1 segmentectomy). Four cases were managed by minimal resections (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The larger biopsy specimens obtained through the rigid bronchoscope can induce serious hemorrhage, but their yield is probably greater. In our review of the literature 587 endoscopic biopsies of carcinoid tumors were found (using both rigid and flexible endoscopes) [1,2,4,5,7,17,18,32,33,[35][36][37]48]. A total of 15 cases of significant hemorrhage were reported, of which 11 required neither transfusion nor operation.…”
Section: Diagnosismentioning
confidence: 99%
“…The larger biopsy specimens obtained through the rigid bronchoscope can induce serious hemorrhage, but their yield is probably greater. In our review of the literature 587 endoscopic biopsies of carcinoid tumors were found (using both rigid and flexible endoscopes) [1,2,4,5,7,17,18,32,33,[35][36][37]48]. A total of 15 cases of significant hemorrhage were reported, of which 11 required neither transfusion nor operation.…”
Section: Diagnosismentioning
confidence: 99%
“…The latest publications have noted that it is suitable to perform parenchyma-sparing resections for proximal and typical carcinoid tumors. [5,16] For example, Machuca et al [11] expressed that the modern management of bronchial carcinoids should consist of parenchyma-sparing procedures whenever feasible, and Ferguson et al [17] concluded that limited resections, such as wedge resections or segmentectomies for peripheral tumors and isolated bronchial sleeve resections or sleeve lobectomies for proximal tumors, should be considered whenever possible for early-stage typical carcinoid tumors because local recurrence is unlikely and the chance of survival is excellent. On the other hand, two of our patients who underwent wedge resections had a peripheral typical carcinoid tumor without lymph node invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2.2 describes four telemedicine projects we identified as the initial pool of projects for the evaluation. (Toledo, Roca, Antón, Martin de Nicolás, Varela, et al, 1989). No formal assessment is available.…”
Section: Identify the Most-successful Existing Telemedicine Projects mentioning
confidence: 99%